Lifetime Analysis of Wireless Sensor Nodes in Different Smart Grid Environments - Eris, Cigdem; Saimler, Merve; Gungor, Vehbi Cagri; Fadel, Etimad; Akyildiz, Ian F. (Springer, 2014)
Wireless sensor networks (WSNs) can help the realization of low-cost power grid automation systems where multi-functional sensor nodes can be used to monitor the critical parameters of smart grid components. The WSN-based smart grid applications include but not limited to load control, power system monitoring and control, fault diagnostics, power fraud detection, demand response, and distribution automation. However, the design and implementation of WSNs are constrained by energy resources. Sensor nodes have limited battery energy supply and accordingly, power aware communication protocols have been developed in order to address the energy consumption and prolong their lifetime. In this paper, the lifetime of wireless sensor nodes has been analyzed under different smart grid radio propagation environments, such as 500 kV substation, main power control room, and underground network transformer vaults. In particular, the effects of smart grid channel characteristics and radio parameters, such as path loss, shadowing, frame length and distance, on a wireless sensor node lifetime have been evaluated. Overall, the main objective of this paper is to help network designers quantifying the impact of the smart grid propagation environment and sensor radio characteristics on node lifetime in harsh smart grid environments.
Fadel, Etimad/0000-0002-7204-9474; Eris, Cigdem/0000-0002-2799-9251;
Keywords: Smart Grid; Wireless Sensor Networks; Lifetime Analysis